Pengaruh Penerapan Prinsip-Prinsip Good Corporate Governance pada Kinerja Bank Perkreditan Rakyat di Kabupaten Badung - Sukardika, I Wayan; Wahyu Purna Anggara, I Wayan Gde; Andika Pradnyana Wistawan, I Made (E-Jurnal Akuntansi; Vol 30 No 8 (2020), 2020)
Transparency, accountability, responsibility, independence and fairness are basic principles in implementing GCG. This study used a survey method with a questionnaire technique that was distributed to 37 BPRs. The sample used was 74 and each of them was taken two respondents from each BPR in the financial section and in the general section in Badung Regency. Determination of the sample using purposive sampling method. The analysis technique used is a simple linear regression analysis using SPSS. This study shows the results that the application of the principles of good corporate governance which includes transparency, accountability, responsibility, independence and fairness has a positive effect on the performance of Rural Credit Banks in Badung Regency. Keywords: Good Corporate Governance; Balanced Scorecard; The Performance.